FRI0447 Cardiovascular risk factors in ankylosing spondylitis. (23rd January 2014) - Vreju, F.; Chisalau, B.; Ciurea, P.; Rosu, A.; Cojocaru-Gofita, I.; Barbulescu, A.; Hoanca, C.; Florea, M.; Musetescu, A.
Abstract : Background: Dyslipidemia (DL) is one the main reason of atherosclerosis and thus, one of the main cardiovascular risk factors in patients with inflammatory arthritis, but data about the connection between DL and ankylosing spondylitis (AS) are limited. Objectives: To evaluate the DL in patients with ankylosing spondylitis and to show the relationship between DL and inflammation in those patients. Methods: 50 patients with AS without cardiovascular diseases were included in the study (mean age ± standard deviation 46, 68±12, 84 years). 45 healthy age-matched controls without inflammatory diseases were examined as well (mean age 45, 08±13, 37). AS activity was expressed using BASDAI index, the number of dactylitis found (0-3 points), the value of ESR and C reactive protein (CRP). Total cholesterol (TC), triglycerides (TG), arterial pressure, BMI and individual cardiac history were noted. Results: Increase of TC was found in patients with AS in comparison with controls (199, 84± 63, 11 vs. 178, 17± 35, 41 mg/dl, p=0, 04). We found an increased value of TG in patients with AS comparative with controls (155, 08 vs 113, 15mg/dl; p< 0, 05). We found no significant correlations between cholesterol/TG and markers of systemic inflammation, but with the disease duration (r=0, 43), which may sugest that not the disease activity at a specific moment has an influence, but the longer exposure to inflammation. There was a correlation between TC and blood pressure (r=0, 51; p<0, 05) and between TC and BMI (r=0, 54; p<0, 05). In the same way, we found a correlation between TG and blood pressure (r=0, 46; p<0, 01). Conclusions: DL is more frequent in SA than in the control group, with a total cholesterol and triglycerides values increased but it is not highly related to disease activity at a specific moment. Disclosure of Interest: None Declared